Organic Fertilization Of Olive Tree Based On Soil Analysis And Foliar Diagnosis: A Case Study Of An Olive Orchard In The Northwest Of Tunisia - Ibrahimi, K.; Gaddas, F. (University of Eloued جامعة الوادي, 2015)
The present study aims at developing an organic fertilization program of an olive orchard located in the North-west of Tunisia. Soil analyses showed an acceptable level of P2O5 and K2O in the soil of the studied farm. Based on leaves and olive fruit analyses, the requirements in N, P and K nutrients of the olive tree for a yield of 20 tons per ha were evaluated at 171 kg N/ha, 40 kg P2O5/ha and 170 kg K2O/ha. As for the required nutrient additions to soil, they were evaluated at 133 kg N/ha, 76 kg P2O5/ha and 264 kg K2O/ha. In order to satisfy the needs of the olive tree, organic compost was used as soil amendement. The required compost amendments have been evaluated to 4 tons/ha at the age of 3/6 years, to 10 tons/ha at the age of 6/10 years and to 20 tons/ha at an age greater than 10 years.
Articale in Journal of fundamental and Applied Sciences Vol. 07, N. 03
Keywords: soil; organic farming; olive tree; foliar diagnosis; fertilization; compost.